The Role of Input-First Preparation in Building EFL Learners’ Public Speaking Confidence - Samsuni, Jazuli (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2025)
This qualitative study explored how input-first preparation influences the public speaking confidence of EFL learners at the University of Insan Budi Utomo. Using a semi structured interview approach, data were gathered from learners who engaged in a preparation sequence emphasizing comprehension before production. Participants were first exposed to authentic speech models, such as TED Talks, and guided through analysis of rhetorical openings, delivery techniques, and language use, prior to producing their own speeches. Findings revealed that this method transformed learners’ perception of public speaking from a high anxiety performance to a skill that can be systematically learned. Students reported reduced anxiety, improved delivery, and greater use of natural intonation and varied sentence structures. The analysis indicated that having a clear opening strategy and exposure to authentic speech rhythms provided psychological readiness and linguistic resources during performance. Compared to traditional output-first methods, the input-first approach offered a lower pressure entry point into speaking tasks which later enables learners to internalize effective techniques before application. The study suggests that input-rich preparation can demystify public speaking, particularly for learners with high speaking anxiety, and positions comprehension as a critical foundation for confident oral communication in EFL contexts.